2022
DOI: 10.3389/fmicb.2022.1003478
|View full text |Cite
|
Sign up to set email alerts
|

FTX271: A potential gene resource for plant antiviral transgenic breeding

Abstract: Flammutoxin (FTX), as well as its precursor TDP, is a protein from Flammulina velutipes with antiviral activity. Transgenic tobacco with the FTX271 (gene of FTX or TDP) can not only delay the onset time of symptoms but also alleviate the symptoms caused by tobacco mosaic virus (TMV), but the mechanism is still unclear. In this study, FTX271 was introduced into Nicotiana benthamiana, and the disease resistance mechanism activated by FTX271 was speculated by transcriptomic and proteomic techniques. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…BAA76510.1) was one of the main proteins in Ffsp-50 . TDP was the precursor of or identical to FTX [ 27 ], which could produce multiple FTX family proteins by partial C-terminal truncation [ 28 ]. Therefore, these findings suggested that FTX was the dominating protein in the different protein fractions except for Ffsp-90 .…”
Section: Resultsmentioning
confidence: 99%
“…BAA76510.1) was one of the main proteins in Ffsp-50 . TDP was the precursor of or identical to FTX [ 27 ], which could produce multiple FTX family proteins by partial C-terminal truncation [ 28 ]. Therefore, these findings suggested that FTX was the dominating protein in the different protein fractions except for Ffsp-90 .…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (qRT-PCR) was performed using the TB Green Premix Ex TapTM II kit (TaKaRa, China) and a CFX96 system (Bio-Rad, USA) under the conditions described in the reagent’s instructions. The primers of the PDS gene are Nb PDSb-F: CGACCAGGTAGCAGCCTATG, Nb PDSb-R: TGGCAGGACCAACAAATGGT, and those of the actin gene are Nb Actin-F: CCTGAGGTCCTTTTCCAACCA and Nb Actin-R: GGATTCCGGCAGCTTCCATT . Three replicates were performed for each biological sample.…”
Section: Methodsmentioning
confidence: 99%
“…The primers of the PDS gene are NbPDSb-F: CGACCAGGTAGCAGCCTATG, NbPDSb-R: TGGCAGGAC-CAACAAATGGT, and those of the actin gene are NbActin-F: CCTGAGGTCCTTTTCCAACCA and NbActin-R: GGATTCCGG-CAGCTTCCATT. 38 Three replicates were performed for each biological sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%